Research on China’s agricultural product sales transformation: online marketing mix strategy and performance on post pandemic area - Zhang, Yaqiong (Frontiers in Sustainable Food Systems, 2024)
At the end of 2019, the sudden outbreak of the pandemic brought a significant impact on the sales of agricultural products in China and all over the world. To reduce the unmarketable problem caused by the pandemic in the agricultural industry, operators who used to focus on offline sales changed their marketing strategy and began to build online sales channels through e-commerce platforms and adopt various online marketing strategies to improve their marketing performance. Furthermore, the performance of online marketing of agricultural products is affected by the interaction of multiple factors in the complex environment. This study aims to distinguish between the performance of different online marketing strategies by using necessary comparative analysis (NCA) and qualitative comparative analysis (QCA) method, to help operators to grasp the critical elements of the online marketing of agricultural products, and how configuration effective impact the online marketing performance. The results show that: (1) NCA’s results show that a single online marketing dimension cannot constitute the necessary conditions for producing high marketing performance of agricultural products, but e-commerce broadcasting, visual effects and government cooperation play an obvious role in improving marketing performance. (2) online marketing performance is influenced by the interaction of various strategies, and no single factor has a significant effect on it. (3) a good online marketing performance configuration path is divided into four, namely “the government cooperation—e-commerce broadcasting” domination; “the government cooperation—visual effects—e-commerce broadcasting” leading; “customer relationship—the government cooperation—visual effects—e-commerce broadcasting” leading; “platform number—visual effects—e-commerce broadcasting” leading. (4) There are four driving paths with no-good online marketing performance, and there is a causal asymmetric relationship of the driving paths with good online marketing performance. This study provides management enlightenment for agricultural operators on how to effectively improve the performance of online marketing, help operators to solve practical problems, and facilitate the development of agricultural e-commerce.